2023
DOI: 10.3390/cleantechnol5030053
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Sustainability of the Most Prominent Type of Marine Diesel Engines under the Implementation of the EEXI and CII Regulations

Dionysios Polemis,
Michael Boviatsis,
Stefanos Chatzinikolaou

Abstract: The wide spread of the Diesel engine has been instrumental in the development of modern shipping. Marine Diesel engines dominate today as an option for the propulsion of commercial ships. While replacing Diesel engines with alternative propulsion engines is difficult to achieve, companies, in light of the new EEXI regulations, are turning to improvements, such as operating at lower rotational speeds, higher maximum combustion pressures, and more efficient overcrowding systems. Τhe purpose of this research pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
1
0
1
Order By: Relevance
“…Ref. [24] evaluated the performance of electronically controlled diesel engines under the newly introduced Energy Efficiency Existing Ship Index (EEXI) and Carbon Intensity Indicator (CII) regulations and found that their efficiency at low loads and overall flexibility can reduce emissions while decreasing OPEX, thereby promoting their adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ref. [24] evaluated the performance of electronically controlled diesel engines under the newly introduced Energy Efficiency Existing Ship Index (EEXI) and Carbon Intensity Indicator (CII) regulations and found that their efficiency at low loads and overall flexibility can reduce emissions while decreasing OPEX, thereby promoting their adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Temos aktualumas. Laivo, kaip ir kitų transporto priemonių, eksploatacijoje svarbu tinkamai paskirstyti lėšas, optimizuoti kaštus bei vykdyti tausojančią įrenginių eksploataciją [1,2]. Balanso išlaikymas tarp tausojančios įrenginių eksploatacijos bei tinkamo kaštų paskirstymo yra svarbus uždavinys transporto parkus eksploatuojantiems valdytojams, kurių pagrindą sudaro įrenginius aptarnaujantys inžinieriai bei finansus valdantys specialistai.…”
Section: įVadasunclassified